Arbuscular mycorrhizal fungi conducting the hyphosphere bacterial orchestra - Zhang, Lin; Zhou, Jiachao; George, Timothy S.; Limpens, Erik; Feng, Gu (Trends in plant science, 2022)
More than two-thirds of terrestrial plants acquire nutrients by forming a symbiosis with arbuscular mycorrhizal (AM) fungi. AM fungal hyphae recruit distinct microbes into their hyphosphere, the narrow region of soil influenced by hyphal exudates. They thereby shape this so-called second genome of AM fungi, which significantly contributes to nutrient mobilization and turnover. We summarize current insights into characteristics of the hyphosphere microbiome and the role of hyphal exudates on orchestrating its composition. The hyphal exudates not only contain carbon-rich compounds but also promote bacterial growth and activity and influence the microbial community structure. These effects lead to shifts in function and cause changes in organic nutrient cycling, making the hyphosphere a unique and largely overlooked functional zone in ecosystems. Arbuscular mycorrhizal (AM) fungi release hyphal compounds into the soil to orchestrate the hyphosphere colonized by a diversity of microbes.The composition of the hyphosphere microbiome is different to bulk soil and rhizosphere.Nutrient cycling in the hyphosphere is affected by the change in microbiome.Shifts in microbial function cause changes in organic nutrient cycling, making the hyphosphere a unique and important functional zone in ecosystems.